(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
That internal control is particularly important in improvingperformance and tax reform، they play an important role in the regularity ofwork and development and the anti corruption and activating the decisionsand tax legislation، as contained in the organizational plan and the means،procedures and components designed from which to ensure a policy andimplementation plans The research aims to review the reality of the internalcontrol in the General Commission for Taxes and stand on the deficiencies init, with the strengthening of the role of internal control in the GeneralAuthority for taxes based on the laws and regulations and by using modernmeans to work as well as developing the performance of employees in thebody، including helping to reform labor taxation. The search resulted to a setof conclusions notably - There is no strategic plan for the development ofbusiness tax in terms of the use of figure-mail and build relationships of trustand continue with the mandate to develop a new mechanism to provide theservice in terms، the reduce a series of procedures، and easeof communication. And the multiplicity of laws and tax legislation، as well asinternal instructions and regulations laid down by the Commission for thepurpose of settling accounts tax which led to the emergence of a gap betweentaxpayers and tax administration، which led to the complexity of theprocedures at work.